TURAICHAN ADJHURI: PERUMUS KALENDER MENARA KUDUS - Jayusman Jayusman (Program Studi Hukum Keluarga Islam, 2013)
One of the legendaries expert in Islamic astronomy (falak) in Indonesia was KH. Turaichan Adjhuri. He was a humble kyai inherited Islamic astronomy developed in pesantren in Indonesia. Although he has passed away long time ago, His master piece of Menara Kudus (Kudus Minaret) almanac, completed by his son, has been used as reference by society until now.Keywords: Turaichan Adjhuri, Menara Kudus almanac, Falak